PELATIHAN KETERAMPILAN BERKOMUNIKASI PADA PEREMPUAN DI PANTI SOSIAL REHABILITASI WANITA TUNA SOSIAL - Hamzah, Hamzah; Herfriady, Herfriady (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2019)
The role of social institutions in communication skills training at the Rehabilitation Social Institution for Women with Social Disabilities in Indralaya, Ogan Ilir Regency, uses a qualitative approach with a descriptive level of explanation. The results showed that the role of social institutions in communication skills training at the Indralaya Women's Rehabilitation Social Institution, Ogan Ilir Regency, had been implemented quite well, but there were still some obstacles that occurred in the field. Obstacles to the Social Rehabilitation of Women with Disability Social Institutions are delays in disbursement of funds for the first quarter, thus hampering all activities from training costs, meals to studying. The Indralaya Women's Rehabilitation Social Institution for Social Rehabilitation really must be monitored by the coaches. Based on the dimensions of clarity of purpose, there are still problems. One of the obstacles is the lack of availability of facilities and infrastructure in dormitories and study rooms at the Indralaya Women's Rehabilitation Social Center. The lack of adequate facilities in the communication skills training class has forced the orphanage coach to deal with it by using equipment and classes in rotation.